Artistic research in the future academy - Butt, Danny (Bristol, UK/Chicago, USA Intellect, 2017)
The rapid growth of doctoral-level art education challenges traditional ways of thinking about academic knowledge and, yet, as Danny Butt argues in this book, the creative arts may also represent a positive blueprint for the future of the university. Synthesizing institutional history with aesthetic theory, Artistic Research in the Future Academy reconceptualizes the contemporary crisis in university education toward a valuable renewal of creative research. AcknowledgementsIntroductionChapter 1: The Transformation of the UniversityChapter 2: The Art SchoolChapter 3: Artistic Research: Defining the FieldChapter 4: Science and Critical SuppressionChapter 5: Critique, Artistic and AestheticConclusion: Exiting Artistic ResearchBibliographyIndex